Analisis Perencanaan Pragmatisme Pada Pemanfaatan Stadion Maulana Yusuf sebagai Sentra Pedagang Kaki Lima (PKL) di Kota Serang Provinsi Banten - Desliana, Wulan (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
This research discusses the application of the pragmatism planning approach in the efforts of the Serang City Government to divert the function of the Maulana Yusuf Stadium supporting area into a center for informal economic activities in the form of stalls or kiosks for street vendors (PKL). The method used is library research, by examining various relevant sources that support planning analysis. This research examines six aspects of planning pragmatism according to Rustiadi et al. namely the role of government and professional planners, the role of society, the role of science, communication, sources of rationality, and views on nature and the environment. The results showed that the stadium revitalization planning process has reflected a pragmatic approach that is adaptive to real problems and community needs, although there are still obstacles such as less than optimal communication and land dispute resolution. In conclusion, this pragmatic planning is able to be a solution that is solutive and flexible in organizing street vendors in an orderly manner without ignoring the stadium's function as a public space. Recommendations include improving two-way communication, legal certainty over land use, and strengthening community participation in the planning process.